From the Liturgical Movement to Pope Francis's Desiderio desideravi: Frederick McManus and His German Colleagues United in Liturgical Formation and Reform - Benini, Marco (The jurist, 2023)
The 2023 McManus Lecture, delivered at The Catholic University of America, honors the prominent canonist and liturgist Monsignor Frederick R. McManus by highlighting his liturgical expertise and merits for the liturgical renewal. McManus notably cooperated with his German colleagues in Trier, Johannes Wagner as the head of the German Liturgical Institute, and Balthasar Fischer, the first chair of liturgical studies in Germany. Based on their letters kept in the archive of the Liturgical Institute in Trier, one can see how these important figures of the liturgical renewal became acquainted at international liturgical study meetings in 1956/60, cooperated as consultants for drafting Sacrosanctum Concilium, engaged in the liturgical reform of the Mass and the baptismal rites, and worked together in promoting liturgical studies. These three protagonists were part of the larger context of the liturgical movement as it existed between Germany and the United States in the early liturgical movement, in which Virgil Michel and immigrants brought ideas from Europe/Germany to the United States and adapted them. While the relationship first was one of influence and support, in the later liturgical movement it became one of cooperation. Pope Francis has recalled our attention to the liturgical movement in Desiderio desideravi, which demonstrates the enduring relevance of these three protagonists and the liturgical formation to which they have contributed.